Circulating Tumor DNA Predicts Pathologic and Clinical Outcomes Following Neoadjuvant Chemoradiation and Surgery for Patients With Locally Advanced Rectal Cancer. (December 2021) - McDuff, Susan G. R.; Hardiman, Karin M.; Ulintz, Peter J.; Parikh, Aparna R.; Zheng, Hui; Kim, Daniel W.; Lennerz, Jochen K.; Hazar‐Rethinam, Mehlika; Van Seventer, Emily E.; Fetter, Isobel J.; Nadres, Brandon; Eyler, Christine E.; et al.
Abstract : PURPOSE : This study was designed to assess the ability of perioperative circulating tumor DNA (ctDNA) to predict surgical outcome and recurrence following neoadjuvant chemoradiation for locally advanced rectal cancer (LARC). MATERIALS AND METHODS : Twenty‐nine patients with newly diagnosed LARC treated between January 2014 and February 2018 were enrolled. Patients received long‐course neoadjuvant chemoradiation prior to surgery. Plasma ctDNA was collected at baseline, preoperatively, and postoperatively. Next‐generation sequencing was used to identify mutations in the primary tumor, and mutation‐specific droplet digital polymerase chain reaction was used to assess mutation fraction in ctDNA. RESULTS : The median age was 54 years. The overall margin‐negative, node‐negative resection rate was 73% and was significantly higher among patients with undetectable preoperative ctDNA (n = 17, 88%) versus patients with detectable preoperative ctDNA (n = 9, 44%; P = .028). Undetectable ctDNA was also associated with more favorable neoadjuvant rectal scores (univariate linear regression, P = .029). Recurrence‐free survival (RFS) was calculated for the subset (n = 19) who both underwent surgery and had postoperative ctDNA available. At a median follow‐up of 20 months, patients with detectable postoperative ctDNA experienced poorer RFS (hazard ratio, 11.56; P = .007). All patients (4 of 4) with detectable postoperative ctDNA recurred (positive predictive value = 100%), whereas only 2 of 15 patients with undetectable ctDNA recurred (negative predictive value = 87%). CONCLUSION : Among patients treated with neoadjuvant chemoradiation for LARC, patients with undetectable preoperative ctDNA were more likely to have a favorable surgical outcome as measured by the rate of margin‐negative, node‐negative resections and neoadjuvant rectal score. Furthermore, we have confirmed prior reports indicating that detectable postoperative ctDNA is associated with worse RFS. Future prospective study is needed to assess the potential for ctDNA to assist with personalizing treatment for LARC.